Structure of Ldt(Mt2), an l,d-transpeptidase from Mycobacterium tuberculosis - Böth, Dominic (International Union of Crystallography, 2013)

(untitled)
The transpeptidase Ltd(Mt2) catalyzes the formation of the (3–3) cross-links characteristic of the peptidoglycan layer in the Mycobacterium tuberculosis cell wall. Bioinformatics analysis suggests that the extramembrane part of the enzyme consists of three domains: two smaller domains (denoted as A and B domains) and a transpeptidase domain (the C domain) at the C-terminus. The crystal structures of two fragments comprising the AB domains and the BC domains have been determined. The structure of the BC module, which was determined to 1.86 Å resolution using Se-SAD phasing, consists of the B domain with an immunoglobulin-related fold and the catalytic domain belonging to the ErfK/YbiS/YbnG fold family. The structure of the AB-domain fragment, which was solved by molecular replacement to 1.45 Å resolution, reveals that despite a lack of overall sequence identity the A domain is structurally very similar to the B domain. Combining the structures of the two fragments provides a view of the complete three-domain extramembrane part of Ldt(Mt2) and shows that the protein extends at least 80–100 Å from the plasma membrane into the peptidoglycan layer and thus defines the maximal distance at which cross-links are formed by this enzyme. The Ldt(Mt)-related transpeptidases contain one or two immunoglobulin domains, which suggests that these might serve as extender units to position the catalytic domain at an appropriate distance from the membrane in the peptidoglycan layer.